Unexpected Dimerizations of Arylfurfural Oximes in their Mass Spectra - Samina Aslam; Aroog Fatima; Sidra Mustafa; Ansa Madeeha Zafar; Noreen Aslam; Mussarat Jabeen; Munawar Ali Munawar; Misbahul Ain Khan (Orbital: The Electronic Journal of Chemistry, 2024)
Various oximes of arylfurfural were found to eliminate an OH radical and dimerize during their mass spectral fragmentaion. A tentative fragmentation pattern is presented.